Media Komik Kesehatan Reproduksi Sebagai Edukasi Menarche Bagi Siswi Madrasah Ibtidaiyah Muhammadiyah - Sodikin Sodikin; Asiandi Asiandi; Deisy Sri Hardini; Sarwito Rachmad Barmawi; Mustiah Yulistiani (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Menarche is an important milestone in female reproductive development, commonly occurring during late childhood or early adolescence. Insufficient knowledge of reproductive health often causes female students to experience anxiety, fear, and unpreparedness when facing their first menstruation. Educational comic books are an age-appropriate medium, presenting health information in an engaging, simple, and understandable format for elementary school students. This community service program aimed to analyze the use of the educational comic book Adolescent Reproductive Health: I Am Ready to Face Menarche in improving knowledge, attitudes, and preparedness for menarche among female students at Muhammadiyah Elementary School (Madrasah Ibtidaiyah Muhammadiyah) Gumiwang. This activity employed a quantitative pre-experimental design using a one-group pretest-posttest approach. Participants consisted of 30 female students in grades 5 and 6 who had not yet experienced menarche and met the inclusion criteria. The intervention consisted of reproductive health education using the comic book, with knowledge, attitude, and preparedness data collected via structured questionnaires before and after the intervention. Bivariate analysis compared participants' scores before and after the program. Results showed the comic book improved students' knowledge, promoted more positive attitudes, and increased preparedness for menarche. It helped students understand the physical and psychological changes of puberty, appropriate menstrual hygiene practices, and boosted confidence in facing their first menstruation. The comic book is a promising medium for improving knowledge, attitudes, and preparedness among female students facing menarche. Age-appropriate educational media should be incorporated into school-based reproductive health education to promote early reproductive health literacy and better preparedness for puberty.